PUBLIC SECTOR HUMAN RESOURCE MANAGEMENT TRANSFORMATION FOR EFFECTIVE AND ACCOUNTABLE GOVERNANCE - Nursaimatussaddiya; Alexander Kotchegura (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2026)
This study aims to analyze the transformation of public sector human resource management in realizing effective and accountable governance in Medan City. The study uses a qualitative descriptive method with a public administration and human resource management approach. Data were obtained through literature study, document analysis, and observation of relevant administrative phenomena related to public sector human resource management, public service delivery, bureaucratic reform, and governance accountability. The findings show that public sector human resource management transformation plays a strategic role in improving local government performance through merit-based management, employee competence development, performance-based assessment, digital administrative reform, and accountability mechanisms. The study also finds that challenges such as uneven employee competence, resistance to change, bureaucratic rigidity, and limited innovation culture may hinder the effectiveness of transformation. The study concludes that public sector human resource management should be positioned as a central agenda in local governance reform. Effective and accountable governance can be strengthened when public employees are professional, competent, adaptive, performance-oriented, and supported by transparent institutional systems.